Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fgene.2019.01098
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Factor X1 Downregulation Contributes to Monocyte Chemoattractant Protein-1 Overexpression in CD14+ Monocytes via Epigenetic Mechanisms in Coronary Heart Disease

Abstract: Monocyte chemoattractant protein 1 (MCP1) affects the chemotaxis of monocytes and is a key chemokine closely related to the development of atherosclerosis (AS). Compared with healthy controls, coronary heart disease (CAD) patients show significantly upregulated plasma concentrations and mRNA expression of MCP1 in CD14+ monocytes. However, the specific regulatory mechanism of MCP1 overexpression in AS is still unclear. Our previous research indicated that there was no significant difference in the H3K4 and H3K2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…4D ). Both of these cells types play crucial roles in vascular dysfunction 67 , while RFX factors are correlated with epigenetic changes in hypertension patients 68 and RFX1 indirectly reduces monocyte recruitment in atherosclerosis 69 . Given motif similarities between RFX factors, further work will be particularly important to understand the role of particular RFX TFs in endothelial and macrophage function.…”
Section: Resultsmentioning
confidence: 99%
“…4D ). Both of these cells types play crucial roles in vascular dysfunction 67 , while RFX factors are correlated with epigenetic changes in hypertension patients 68 and RFX1 indirectly reduces monocyte recruitment in atherosclerosis 69 . Given motif similarities between RFX factors, further work will be particularly important to understand the role of particular RFX TFs in endothelial and macrophage function.…”
Section: Resultsmentioning
confidence: 99%
“…In coronary heart disease or coronary artery disease, RFX1 was shown to influence CD14 + monocytes via epigenetic processes, [48,49] whereas its role in bone metabolism-related diseases or the process of bone formation has not been fully investigated. Thus, we revealed a unique and crucial function for RFX-1 in the control of elevated IL-17A production in CD4 + T lymphocytes treated with MS, which encouraged osteogenic differentiation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that HDAC1 plays a vital role in cell proliferation and differentiation, cell cycle regulation as well as tissue transformation and development [ 22 26 ]. In addition, HDAC1 is found increased in various cancers, nervous system and heart diseases, and so on [ 27 29 ]. HDAC1 level is also elevated in lungs from human idiopathic PAH and rats with PAH; class I HDACs participate in the ECM remodeling of various tissues through different molecular mechanisms [ 8 , 9 , 30 ].…”
Section: Discussionmentioning
confidence: 99%